Health Promotion for Older Persons in the Community - Na Wichian, Sureerat; Rattana-umpa, Juthamas (Dhammathas Academic Journal, 2022)
Health promotion is a crucial part of healthcare, as it reduces disease incidence, strengthens the body and prevents illnesses leading to disability and premature death of population of the world, especially it will benefit more for the older persons who are considered both physically and mentally frail. This article aims to review the literatures on the approaches to health promotion for the older persons in the community, including situation and demographic structure analysis, the importance of health promotion, concept of health promotion in the older persons and the role of relevant personnel in the health promotion on a community basis. It is our objective to incorporate these background knowledges to enhance the health of the older persons in the community.